Composting for managing dogs’ corpses - Valente, Beatriz Simões; Xavier, Eduardo Gonçalves; Pilotto, Marcus Vinícius Tabeleão; Pereira, Heron da Silva (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2015)
A trial was conducted to evaluate the contribution of composting for managing dogs’ corpses. Treatment was carried out in a composting cell (2.20m length, 1.70m width, 1.20m height and 2.50m ceiling). Corpses and wood shavings were mixed at 2:1 ratio. Data were analyzed with ANOVA and polynomial regression and the means were compared by the Student Newman Keuls test at 5%. The results showed that composting is an efficient alternative for managing of dogs’ corpses and that more than 90 days are needed for its complete decomposition. The intact structure of wood shavings at the end of process along with the high C/N ratio during the 90 days of composing suggests that a higher proportion of the proteic source could have been used